The Collaboration Of TOE Framework And Vocational Faculty Unair’ Support Social Media Management Team - Gagas Aji; Alifian Sukma; Amanda Dyla Pramadanti (UPY Business and Management Journal (UMBJ), 2022)
Abstract: It is necessary to expand social media's involvement in higher education branding, especially for vocational school. This promotional and branding is consistent with the Ministry of Education and Culture's vision. All vocational education institutes are supported and urged by the Director-General of Vocational Studies to inform the public about their advantages constantly. Undoubtedly, a social media management team is needed to manage this. It should be noted that the difficulties ahead are not becoming any simpler. Therefore, it has become more important than ever to work with the leadership of the vocational faculty's social media team. The researcher assumed that TOE and leadership shamans could be sufficient to raise public awareness of the Airlangga University Vocational Faculty's increased branding efforts. Purpose: The function of social media management implementation cannot be isolated from the effect of numerous parties and instruments. The TOE framework describes the management and motivation of social media adoption as a lens. Methodology: Case studies were used in this research. This research employs qualitative methodologies in data collecting through interviews: interviews and document searches to provide a clear image of the Vocational Faculty's social media team implementation at Universitas Airlangga. Findings: Besides being supported by technological, organizational, and environmental factors, the leadership's participation is worthy of discussion. The leadership did not hesitate to discuss and decide the direction of the social media team of the Vocational Faculty of Airlangga University.